EFFECTS OF DILUTION AND AGITATION ON EUCALYPTUS PELLITA ESSENTIAL OIL EXTRACTION - Kemas Muhammad Bagus; Muhammad Rifqi Syaghaf; Lia Cundari (Walisongo Journal of Chemistry, 2026)
Eucalyptus pellita essential oil is commonly extracted by hydrodistillation; however, this process has limited efficiency due to heat and mass-transfer constraints. Process parameters, such as solvent loading and agitation, offer promising but understudied opportunities for process intensification to improve oil yield and quality. This study aimed to analyze the interactive effects of the leaf-to-solvent mass ratio and agitation speed on the extraction yield and chemical profile of E. pellita essential oil obtained through hydrodistillation. Extraction was performed using 150 g of chopped E. pellita leaves with particle sizes of 0.1–0.5 cm at 100°C for 4 hours under atmospheric pressure. The independent variables were leaf-to-solvent mass ratios of 1:4, 1:6, and 1:8, and agitation speeds of 300, 600, and 900 rpm. The extracted oil was quantified based on yield and chemical composition. The chemical profile of the essential oil was characterized using gas chromatography–mass spectrometry (GC–MS). The results showed that solvent proportion had a more significant effect than agitation speed. The 1:8 ratio produced the highest oil mass of 0.62 g and yield of 0.41%. GC–MS analysis identified α-pinene, eucalyptol (1,8-cineole), L-α-terpineol, caryophyllene, and bicyclo[3.1.1]heptane as the major components. This study demonstrates the decoupled effects of solvent ratio and agitation in E. pellita hydrodistillation, revealing the solvent ratio as a chemical driver of compositional selectivity and agitation speed as a physical driver of system homogeneity. This distinction provides a targeted strategy for simultaneously optimizing extraction yield and oil quality.